2013
DOI: 10.1016/j.joca.2013.02.307
|View full text |Cite
|
Sign up to set email alerts
|

FX006 prolongs the residency of triamcinolone acetonide in the synovial tissues of patients with knee osteoarthritis

Abstract: reading method. Responders (patients with no relevant progression) were defined as those with a JSW loss between baseline and End, lower than 0.1 mm (JSN >-0.1 mm), or 0.2 mm (JSN >-0.2 mm) or 0.3 mm (JSN>-0.3 mm). Patients who withdrew from the study were counted as non-responder patients. SrRan 1g and SrRan 2g treatment groups were compared to placebo in the FAS using a chi 2 test. Results: The ITT set included 1371 (82%) patients. Age was 63AE7 years, BMI was 30AE5 kg/m2, JSW was 3.5AE0.8 mm. 61% were KL II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Even the 80 mg of bolus TAA administered in arthritic knees in several clinical studies did not result in adverse effects (C. E. Chavez‐Chiang et al, ; N. R. Chavez‐Chiang et al, ; Kumar, Dhir, Sharma, Sharma, & Singh, ; Popma et al, ). Moreover, the IA release of a dose of 60‐mg TAA from a PLGA MS platform, equivalent to the lowest dosage used in the current study, was shown to be safe in knee OA patients (Bodick et al, ). Also in a different, collagenase‐induced, rat model of OA, the extended release of TAA by PEA MSs did not show any effects on cartilage integrity nor induced tissue calcification (Rudnik‐Jansen et al, ).…”
Section: Discussionmentioning
confidence: 69%
“…Even the 80 mg of bolus TAA administered in arthritic knees in several clinical studies did not result in adverse effects (C. E. Chavez‐Chiang et al, ; N. R. Chavez‐Chiang et al, ; Kumar, Dhir, Sharma, Sharma, & Singh, ; Popma et al, ). Moreover, the IA release of a dose of 60‐mg TAA from a PLGA MS platform, equivalent to the lowest dosage used in the current study, was shown to be safe in knee OA patients (Bodick et al, ). Also in a different, collagenase‐induced, rat model of OA, the extended release of TAA by PEA MSs did not show any effects on cartilage integrity nor induced tissue calcification (Rudnik‐Jansen et al, ).…”
Section: Discussionmentioning
confidence: 69%
“…In a previous clinical study, the 40-mg dose of FX006 demonstrated maintenance of synovial concentrations of triamcinolone acetonide consistent with pharmacologic activity for a period of at least six weeks, when levels of triamcinolone acetonide produced by an equivalent dose of immediate-release triamcinolone acetonide were below the limits of quantitation 19 . Not only did FX006 prolong the maximal effect of immediaterelease triamcinolone acetonide (which in the present study occurred at four weeks), but also, between two and eleven weeks, the analgesic effect of 40-mg FX006 exceeded the maximal effect of immediate-release triamcinolone acetonide at four weeks and was significantly superior to immediate-release triamcinolone acetonide from five weeks to ten weeks (p < 0.05 at each time point), with a mean pain reduction relative to immediate-release triamcinolone acetonide of 20.9 on the 11-point Numeric Rating Scale.…”
Section: Discussionmentioning
confidence: 85%
“…Loss of Efficacy at Six Weeks with the 60-Mg Dose I n a companion pharmacokinetic study, measurement of synovial triamcinolone acetonide concentrations at six weeks in patients revealed markedly lower levels at the 60-mg dose (with a geometric mean of 17,546 pg/mL) than the 40-mg dose (78,757 pg/mL) 19 . The loss of efficacy of the 60-mg FX006 dose may be associated with premature release of triamcinolone acetonide from the PLGA matrix at one through six weeks.…”
Section: Appendixmentioning
confidence: 96%
See 1 more Smart Citation
“…Overall, particle-based delivery systems have the potential to increase drug residence times greatly, with 10–30-fold increases reported in pre-clinical models. A clinical study reported in 2013 of a PGLA-encapsulated corticosteroid, triamcinolone acetonide (FX006, Flexion Therapeutics), demonstrated residence in the joint space at therapeutic concentrations at 6 weeks after injection, 137 providing some evidence of even longer periods of sustained release for microcapsules. Nevertheless, no particle-based or liposome drug-delivery system has yet advanced past clinical trials for intra-articular drug delivery in the USA, possibly because of the need to establish cost-effective manufacturing processes and dosing strategies.…”
Section: Intra-articular Therapeuticsmentioning
confidence: 99%